The Processes of Learning and Teaching Cimbveka: Enhancing Music Education Practices in Primary Schools of the Southern Region of Mozambique - Gove, Joaquim Borges Armando (College of Music, 2022)
This study investigates cimbveka as part of Mozambican Copi people's indigenous music as well as the processes involved in teaching and learning the music. Cimbveka is an entertainment genre of traditional reed-pipe music that integrates song ('ndando). The reed pipes are played and the song performed interchangeably, making cimbveka a two-part music performance. For this study, I took cimbveka to formal education settings with the aim to unveil and to understand its pedagogic potential to music education. I applied ethnographic methods as the main research method in ethnomusicological and educational research. As part of ethnographic methods, the participant observation method allowed me to engage with the participants by closely observing and interacting with the participants. During the observation process I used conversational interviews to collect information both in formal educational settings and in community settings. This was appropriate to gather valuable information regarding aspects difficult to observe. Thus, using open-ended questions, commenting about the events and paying special attention to occasional conversation between participants, triggered the informants to talk about several issues that helped in making sense of the data collected. In addition to conversational interviews, I used the Community of Philosophical Enquiry (CPE) to grasp the participants' thoughts regarding music education, as well as their understanding about traditional music. While participant observation was useful for data collection, the combination of ethnographic content analysis and the constructivist paradigm was useful to analyse the data. The ethnographic content analysis was important in interpreting the information collected through the CPE and conversational interviews as those data carried more of the participants' subjectivity, and the constructivist paradigm was useful to understand the social interactions around the cimbveka learning processes. The results reveal cimbveka as a holistic concept in music knowledge transmission as its performance features particular musical aspects such as rhythm, melody, pulse, tempo, and so forth, distinctly. The remarkable distinctiveness of these musical elements in cimbveka performance makes cimbveka practice a scaffolding tool to music learning. In addition, once cimbveka is learned mostly by imitation and repetition with the aid of formative assessment, this study concludes that learning and teaching within cimbveka practices is constructivist and phenomenological. This makes cimbveka a powerful tool to enhance music education in both processes of learning and teaching.